Pengaruh Perceived Risk, Cost Saving, Dan Time Saving Terhadap Kepuasan Pelanggan Pada Pembelian Tiket Pesawat Online Di Situs Www.Tiket2.Com - Septi Ambarwati; Endro Isnugroho (Journal of Tourism and Economic, 2018)
This research explains the effect of perceived risk, cost saving, and time saving on customer satisfaction on the purchase of airline tickets online through website www.tiket2.com. .It is based on information technology quality in selling tickets online by providing features that are very easy to use, and give serious attention to the security of customer data and ease in transacting. This research uses non probability sampling method with the criteria used in sample selection is customer who make ticket purchase through website www.tiket2.com. The data used in this study is primary data obtained directly from respondents through interviews and filling questionnaires. From the results of research proved perceived risk, cost saving, and time saving have a positive and significant impact on customer satisfaction. The contribution of this research is expected to be as an input and guide for management practitioners in carrying out business activities, especially those related to factors that influence customer satisfaction, that is, to provide input in decision making at giving satisfaction to the customer.